Pendidikan Kewarganegaraan melalui Program Bela Negara: Perspektif Mahasiswa Mencintai Tanah Air dan Bangsa (Studi Kasus Mahasiswa Program Studi PGSD Universitas Muhammadiyah Palangkaraya) - Ady Ferdian Noor (Pedagogik: Jurnal Pendidikan, 2016)
The reality, Student of Study Program PGSD FKIP UM Palangkaraya less cognitive develop an attitude which is less highly motivated to do something, lacking want to engage in activities that add competence, less vibrant, less organized, less accomplished, less empathy for social activities and less creative. These problems need to be addressed by the State Defense Program. In the current conditions of defending the country should be interpreted more real acts. The State Defense Program is not only identified with the lift arms but must be interpreted more broadly, that is to defend the country in many ways adapted to the professional ability of each. Come with the name of the nation through achievements in various fields are also included defending the country. Chaidir Basrie suggested that civil defense is an attitude, determination, and citizen action that regular, comprehensive, integrated and continues based on the love of the homeland, the consciousness of nation and state of Indonesia, beliefs and magic Pancasila as the state ideology , In Indonesia, efforts to defend the state as expressly provided in the Constitution of 1945 article 27 paragraph 3 which states that "every citizen has the right and duty to participate in the defense efforts of the state". Thus every citizen is expected to take an active part in defending the country. State Defense Program which is a non-physical activity or non-militarism is an integrated part in all courses/subjects so that these programs should receive priority attention to developing conative nature that ultimately can improve the students love for the homeland and the nation. Students have not been able to show fully the nature cognitive that can encourage a love of the homeland and the nation because they are less energetic, less creative, and less highly motivated indeveloping competency activities.